ECONOMIC FACTORS OF CLINICAL TRIALS OF MEDICINES IN SMALL POPULATION COUNTRIES: CASE STUDY OF LATVIA - Pētersone, Māra; Krieviņš, Dainis; Ketners, Kārlis; Rakauskienė, Ona Gražina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The clinical trial process has become a significant type of services that provides huge added value to any national economy. Undoubtedly, the primary group of stakeholders in clinical trials of medicines is pharmaceutical companies that obtain a product as a result of successful clinical trials. However, other groups involved will also obtain materials and intangible benefits from the process of clinical trials of medicines. In this context, the authors tended to find out: What are considered to be the primary economic benefits of clinical trials of medicines in a society with small population? Aim of the research is to analyse economic factors of clinical trials of medicines in countries with small population, taking Latvia as an example. Object of the research: economic factors of clinical trials of medicines. The principle of snowball has been used to make the selection of the participants' survey. The empirical analysis and evaluation of economic factors in unique clinical trials of medicines are based on the qualitative research method of semi-structured individual (in-depth) interviews. According to the survey, the most important economic type of clinical trials of medicinal products in Latvia is “socioeconomic factors”, the average index of the factor being 0.82. The most significant three categories of the socioeconomic factors are “Access to the latest treatment methods and preparations” (Index max 1), “Improved patient care (time used per patient)” (Index 0.87) and “Exchange of experience, transfer of knowledge on the most innovative treatment methods” (Index 0.86). Society with small population values the primary economic benefits from clinical trials of medicines. It can be concluded that the socioeconomic factor is the most significant, compared to the direct economic factor and the alternative cost savings factor.